Modulating Effects of Pycnogenol® on Oxidative Stress and DNA Damage Induced by Sepsis in Rats - Taner, Gokce; Basaran, A. Ahmet; Basaran, Nursen; Sarigol, Zehra; Bacanli, Merve; Aydin Di̇lsi̇z, Sevtap; Sahin, Tolga (Wiley, 2014)
The aim of this study was to evaluate the protective effects of Pycnogenol® (Pyc), a complex plant extract from the bark of French maritime pine, on oxidative stress parameters (superoxide dismutase (SOD), and glutathione peroxidase (GPx) activities and total glutathione (GSH) and malondialdehyde (MDA) levels), an inflammatory cytokine (tumor necrosis factor alpha (TNF‐α) level) and also DNA damage in Wistar albino rats. Rats were treated with 100 mg/kg intraperitonally Pyc following the induction of sepsis by cecal ligation and puncture. The decreases in MDA levels and increases in GSH levels, and SOD and GPx activities were observed in the livers and kidneys of Pyc‐treated septic rats. Plasma TNF‐α level was found to be decreased in the Pyc‐treated septic rats. In the lymphocytes, kidney, and liver tissue cells of the sepsis‐induced rats, Pyc treatment significantly decreased the DNA damage and oxidative base damage using standard alkaline assay and formamidopyrimidine DNA glycosylase‐modified comet assay, respectively. In conclusion, Pyc treatment might have a role in the prevention of sepsis‐induced oxidative damage not only by decreasing DNA damage but also increasing the antioxidant status and DNA repair capacity in rats. Copyright © 2014 John Wiley & Sons, Ltd.
Keywords: Flavonoids; Glutathione Peroxidase; Plant Extracts; Superoxide Dismutase; Tumor Necrosis Factor-alpha; Kidney; Pinus; Glutathione; Oxidative Stress; Liver; Malondialdehyde; Sepsis; Animals; Rats, Wistar; DNA Damage; 3. Good health